2018
DOI: 10.1021/acsanm.8b00137
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Double Rare Earth-Doped Carbon Dots for MRI/CT/FI Multimodal Imaging

Abstract: The integration of different imaging functions into an ultrasmall nanoplatform with excellent biocompatibility and metabolic performance to fabricate multimodal imaging probes has been a tremendous challenge. Herein, a novel kind of gadolinium-and ytterbium-doped carbon dots (Gd/Yb@ CDs) with diameter of 5.26 ± 0.93 nm was obtained by the convenient one-step hydrothermal process for magnetic resonance imaging (MRI), X-ray computed tomography (CT), and fluorescent imaging (FI). The obtained Gd/Yb@ CDs exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 40 publications
2
49
0
Order By: Relevance
“…After intravenous injection, I-doped CDs were distributed throughout the body datable by X-ray CT imaging and excreted by renal clearance. Gd/Yb@CDs were synthesized from Na 2 EDTA, GdCl 3 , YbCl 3 , and L-arginine by hydrothermal method [85]. Gd/Yb@CDs exhibited blue emission, and higher longitudinal relaxivity (r 1 = 6.65 mM −1 s −1 ) and excellent X-ray absorption performance (45.43 HU l g −1 ).…”
Section: Multimodal Imagingmentioning
confidence: 99%
“…After intravenous injection, I-doped CDs were distributed throughout the body datable by X-ray CT imaging and excreted by renal clearance. Gd/Yb@CDs were synthesized from Na 2 EDTA, GdCl 3 , YbCl 3 , and L-arginine by hydrothermal method [85]. Gd/Yb@CDs exhibited blue emission, and higher longitudinal relaxivity (r 1 = 6.65 mM −1 s −1 ) and excellent X-ray absorption performance (45.43 HU l g −1 ).…”
Section: Multimodal Imagingmentioning
confidence: 99%
“…This application is based on their photoluminescence properties, 296,297 although they can be hybridized with other particles for use in other imaging modalities. [298][299][300] Bioimaging can both provide basic knowledge about biological systems and used in diagnostic methods. Bioimaging is one of the pivots of theranostics, and since GQDs and CQDs are suitable cargo carriers and demonstrate other therapeutic activities including photothermal therapy and photodynamic therapy, showing bioimaging capabilities, they are promising theranostic agents.…”
Section: Bioimaging Applicationsmentioning
confidence: 99%
“…The r1 value of Gd-CDs As a rising star of carbon nanomaterial, carbon quantum dots (CDs) have drawn tremendous attention because of their excellent optical property, high physicochemical stability, good biocompatibility, and the ease of surface functionalization [53][54][55][56][57]. Recently, various Gd 3+ -doped CDs (Gd-CD) have been synthesized for fluorescence/MR dual-mode imaging by the low temperature pyrolysis of precursors containing Gd 3+ (such as Gd 3+ -complexes) and carbon [58][59][60][61]. Zou and coauthors reported Gd-CD-based theranostics for MRI-guided radiotherapy of a tumor (as shown in Figure 5) [58].…”
Section: Gadolinium (Iii)-complex-based Compositesmentioning
confidence: 99%